Porous antimicrobial crosslinked film of hydroxypropyl methylcellulose/carboxymethyl starch incorporating gallic acid for wound dressing application - Pitpisutkul, Vipawan; Prachayawarakorn, Jutarat (My University, 2024)
Because of weak mechanical qualities and low degree of swelling of hydroxypropyl methylcellulose/carboxymethyl starch (HP/CMS) blended films for wound dressing application, this work prepared a unique antimicrobial crosslinked film utilizing succinic acid (SA) as a non-toxic crosslinker and gallic acid (GAL) as an antibacterial agent. It was observed that the infrared-shifted peak position of O[sbnd]H stretching and bending in HP/CMS/SA/GAL films was caused by hydrogen bond formation among HP, CMS and GAL components. The antimicrobial crosslinked films considerably enhanced their mechanical properties and swelling degree. After adding SA and GAL, the films retained their porosity structure as observed by scanning electron images. Moreover, GAL-loaded HP/CMS/SA films could inhibit Staphylococcus aureus and Escherichia coli growth, showing their wound dressing potential. Crystallinity percentage, water vapor transmission rate, gel fraction, water solubility, water uptake and cytotoxicity were also investigated.
Keywords: Cellulose; Gallic acid; Starch; Wound dressing